Chlorophyll ‘a’ fluorescence Induction kinetics of Ipomoea pes-caprae Sweet, under salinity stress - S. Sridevi, A. Venkatesan (Journal of Phytology, 2009)
The present investigation was made to the effect of exogenous addition of different concentrations of NaCl (100 Ã¢â‚¬â€œ 500mM) and NaCl:CaCl2 (100mM + 1mM to 300mM + 3mM) on growth and photochemical activities of Ipomoea pes-caprae. The upper limit of NaCl and NaCl:CaCl2 salinity for the survival of this seedlings at 500mM NaCl and 300mM + 3mM NaCl:CaCl2 and the favourable growth was observed at 200mM NaCl and 100mM + 1mM NaCl:CaCl2 respectively. Beyond these concentrations the growth rate was declined sharply. The polarographic measurements with isolated mesophyll cell showed enhanced activities of PSI (DCPIPH2ÃƒÂ MV), PSII (H2OÃƒÂ DCPIP) and whole chain electron transport (H2OÃƒÂ MV) upto optimum salinity level of both treatments. At higher salinities, all the photochemical activities reduced drastically. Fast and slow cholorphyll Ã¢â‚¬ËœaÃ¢â‚¬â„¢ fluorescence transients were recorded using intake leaves obtained from control and saline treated plants. Various levels of slow chl Ã¢â‚¬ËœaÃ¢â‚¬â„¢ fluorescence induction kineticsÃ‚Â Ã‚Â Ã‚Â (P, P-S, M, T) showed an increasing activity at 200mM NaCl and 100mM + 1mM NaCl:CaCl2 and thereafter its gradually declined. P/T was directly measured as photosystem II activities. The similar trend was followed to fast chlorophyll Ã¢â‚¬ËœaÃ¢â‚¬â„¢ fluorescence at different levels such as Fo, Fv, Fm and the ratio Fv/Fm significantly enhanced the rate of photosynthetic activities upto optimal level of both salinity.